2009
DOI: 10.1016/j.ocl.2008.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Perfusion with Contrast-Enhanced Magnetic Resonance Imaging

Abstract: Osteoarthritis and avascular necrosis are common clinical entities with unknown etiologies. Recently, vascular changes have been implicated in the pathogenesis of both conditions. This review discusses the use of novel non-invasive imaging techniques, using dynamic contrast-enhanced magnetic resonance imaging, as a means of assessing bone perfusion and therefore quantifying differences seen in both osteoarthritis and avascular necrosis. We have found changes in fluid dynamics in both osteoarthritis and avascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 17 publications
2
23
0
1
Order By: Relevance
“…Contrast elimination reflects venous stasis and intraosseous hypertension as a consequence of venous outflow obstruction. The finding of a significant association with BML size and the rate of contrast elimination is consistent with previous work on perfusion parameters that point to outflow obstruction as the primary change in kinetic parameters 24 . These authors demonstrated that perfusion out of the ROI was significantly lower in BMLs when compared with normal bone.…”
Section: Discussionsupporting
confidence: 90%
“…Contrast elimination reflects venous stasis and intraosseous hypertension as a consequence of venous outflow obstruction. The finding of a significant association with BML size and the rate of contrast elimination is consistent with previous work on perfusion parameters that point to outflow obstruction as the primary change in kinetic parameters 24 . These authors demonstrated that perfusion out of the ROI was significantly lower in BMLs when compared with normal bone.…”
Section: Discussionsupporting
confidence: 90%
“…There are clues that BML may precede changes in cartilage morphology42 and may also predict or be linked to the progression of structural changes in knee OA 3 20 28 43. Our findings documented a significant negative correlation between BML score and cartilage volume in all three compartments at baseline.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, these results confirm the need for some caution in the interpretation of apparently normal T1 and T2 signal areas in human AVN conditions such as Kienböck's disease, particularly in correlating signal changes in conventional MRI to the presence of blood flow. The use of contrast-enhanced MRI may offer more reliable information on bone perfusion [17,29].…”
Section: Discussionmentioning
confidence: 99%